2011
DOI: 10.1111/j.1471-4159.2011.07559.x
|View full text |Cite
|
Sign up to set email alerts
|

D2‐Dopamine receptors target regulator of G protein signaling 9‐2 to detergent‐resistant membrane fractions

Abstract: Detergent-resistant membranes (DRM) are thought to contain structures such as lipid rafts that are involved in compartmentalizing cell membranes. We report that the majority of D2-dopamine receptors (D2R) expressed endogenously in mouse striatum or expressed in immortalized cell-lines is found in DRM. In addition, exogenous co-expression of D2R in a cell line shifted the expression of regulator of G protein signaling 9-2 (RGS9-2) into DRM. RGS9-2 is a protein that is highly enriched in the striatum and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Lipid rafts are a well-known but poorly understood platform for modulating certain protein-protein interactions in neurons as well as affecting GPCR ligand sensitivity, membrane trafficking, and signaling (Allen et al, 2007;Korade and Kenworthy, 2008;Björk and Svenningsson, 2011;Kong et al, 2011;Sebastião et al, 2011;Celver et al, 2012). Lipid rafts would readily enable cross-talk between the D 1 R and D 2 R and could assist in the multifaceted signaling profile of the D 1 -D 2 receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts are a well-known but poorly understood platform for modulating certain protein-protein interactions in neurons as well as affecting GPCR ligand sensitivity, membrane trafficking, and signaling (Allen et al, 2007;Korade and Kenworthy, 2008;Björk and Svenningsson, 2011;Kong et al, 2011;Sebastião et al, 2011;Celver et al, 2012). Lipid rafts would readily enable cross-talk between the D 1 R and D 2 R and could assist in the multifaceted signaling profile of the D 1 -D 2 receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we had reported that D2R co-expression alters the subcellular distribution of G␣ i1 in HEK293T cells (19). In the absence of D2R, the expression of the G␣ i1 is spread out uniformly through the cytoplasm, and upon D2R co-expression, it moves toward the cell boundaries (19).…”
Section: Confocal Microscopy Examination Of the Cellular Localizationmentioning
confidence: 99%
“…We previously showed that the vast majority of D2R expressed in the brain is uniquely resistant to detergent solubilization (19) and wanted to explore the biological significance of our observation. We utilized a novel in-cell biotin transfer assay involving the Escherichia coli biotin ligase enzyme, BirA, that specifically attaches biotin to a unique acceptor peptide (AP) (20).…”
mentioning
confidence: 99%
“…For instance, exogenously increasing membrane cholesterol level in striatal synaptosomes and neuronal-like MN9D cells increases the binding B max values for cocaine analogs but had no effect of DAT surface level [51]. Moreover, cholesterol depletion with MβCD significantly reduced the ability of DAT to take up dopamine without altering DAT surface expression in LLC-PK1, HEK293 and N2A cells [40,41,44].…”
Section: Cholesterol Content and The Function Of Transporters/ Receptorsmentioning
confidence: 99%
“…D1Rs and caveolae can form a functional complex in lipid rafts and regulate D1R-mediated G protein signaling. Similar to D1Rs, D2Rs are also primarily localized in lipid raft microdomains in HEK293 cells and mouse striatum tissues [51,52] although it is unknown whether D2Rs physically interact with certain raft-associated proteins. Moreover, dopamine-induced D2R internalization is largely restricted to D2Rs localized in lipid rafts [53].…”
Section: Sphingolipids and Gangliosidesmentioning
confidence: 99%